KEPEMIMPINAN KEPALA MADRASAH DALAM OPTIMALISASIKUALITAS SARANA DAN PRASARANA PENDIDIKAN DIMADRASAH TSANAWIYAH SWASTA NURUNNAJAHKABUPATEN BATANGHARI PROVINSI JAMBI - Martinis Yamin; Try Susanti; Wahyu Hidayat; Muhammad Nurdiansyah; Desi Ansari; Ninda Dwi Lestari (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to discuss the leadership of the madrasah principal in optimizing the quality of educational facilities at Madrasah Tsanawiyah Swasta Nurunnajah in Batanghari Regency, Jambi Province. The research employs a qualitative method with an exploratory descriptive approach. Data collection techniques include observation, interviews, and documentation. The data analysis process involves data reduction, data presentation, and conclusion drawing. The findings indicate that the effectiveness of the madrasah principal in improving educational facilities has been optimal. This is reflected in their leadership approach, support, and role as a model for the madrasah community in maximizing the available resources. The management of educational facilities under the principal's administration follows a structured process, including planning, procurement, recording, maintenance, and utilization. However, financial limitations remain a significant challenge. The main obstacles faced by the principal include budget constraints that hinder the maintenance and enhancement of facilities, as well as the lack of awareness among the madrasah community regarding the efficient use of educational resources.